2011
DOI: 10.1016/j.cmet.2010.12.004
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of SREBP by a Small Molecule, Betulin, Improves Hyperlipidemia and Insulin Resistance and Reduces Atherosclerotic Plaques

Abstract: Sterol regulatory element-binding proteins (SREBPs) are major transcription factors activating the expression of genes involved in biosynthesis of cholesterol, fatty acid and triglyceride. In this study, we identified a small molecule, betulin, that specifically inhibited the maturation of SREBP by inducing interaction of SREBP cleavage activating protein (SCAP) and Insig. Inhibition of SREBP by betulin decreased the biosynthesis of cholesterol and fatty acid. In vivo, betulin ameliorated diet-induced obesity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
265
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 346 publications
(284 citation statements)
references
References 38 publications
16
265
0
3
Order By: Relevance
“…Consistent with previous reports [34][35][36] , we observed that the mRNA levels of SREBP-1c and SREBP-2, and their target genes, were increased in the liver of long-term high-fat-dietfed mice. The beneficial effects of ZJ001 on metabolic parameters were reflected by its effects on gene expression changes in the liver of mice.…”
Section: Zj001 Regulated the Expression Of Metabolic Genes In Vivosupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with previous reports [34][35][36] , we observed that the mRNA levels of SREBP-1c and SREBP-2, and their target genes, were increased in the liver of long-term high-fat-dietfed mice. The beneficial effects of ZJ001 on metabolic parameters were reflected by its effects on gene expression changes in the liver of mice.…”
Section: Zj001 Regulated the Expression Of Metabolic Genes In Vivosupporting
confidence: 81%
“…Decreased cholesterol biosynthesis increases LDL-receptor levels, which results in a positive cycle for lowered cholesterol levels in serum. However, statins cannot decrease fatty acid biosynthesis because they block the cholesterol biosynthesis that stimulates SREBP activity [36] . The above deficiency of the statin drugs might be compensated for if candidates that specifically modulate the SREBP pathway are identified.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this possibility, inhibition of SREBP was found to ameliorate diet‐induced cholesterol/lipid tissue accumulation and insulin resistance (Tang et al. 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Animal protocols and adenovirus-mediated expression of EGFP, NPC1L1-EGFP, NPC1L1⌬NTD-EGFP, and NPC1L1(L216A)-EGFP in mice liver as well as measurement of cholesterol, phospholipid, or triglyceride in the bile, liver, or plasma were described previously (7,21 (15,18,19). Briefly, HEK293T cells were grown in a monolayer at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%